2015
DOI: 10.1523/jneurosci.2405-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

CCR2 Antagonism Alters Brain Macrophage Polarization and Ameliorates Cognitive Dysfunction Induced by Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is a major risk factor for the development of multiple neurodegenerative diseases. With respect to the increasing prevalence of TBI, new therapeutic strategies are urgently needed that will prevent secondary damage to primarily unaffected tissue. Consistently, neuroinflammation has been implicated as a key mediator of secondary damage following the initial mechanical insult. Following injury, there is uncertainty regarding the role that accumulating CCR2 ϩ macrophages play in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
293
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(315 citation statements)
references
References 71 publications
17
293
3
2
Order By: Relevance
“…Blood-borne monocytes have been shown to infiltrate damaged or diseased brain tissue in animal models of other human neurological disease, such as the EAE model of multiple sclerosis (35), Alzheimer's disease (27,28,44), and traumatic brain injury (13,45). Previous studies have also reported elevated numbers of peripheral immune leukocytes after epileptiform activity (46,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood-borne monocytes have been shown to infiltrate damaged or diseased brain tissue in animal models of other human neurological disease, such as the EAE model of multiple sclerosis (35), Alzheimer's disease (27,28,44), and traumatic brain injury (13,45). Previous studies have also reported elevated numbers of peripheral immune leukocytes after epileptiform activity (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…We found several benefits on disease outcome by preventing entry of CCR2 + monocytes into the brain, including dampened inflammation, reduced number of Iba1 + myeloid cells, ameliorated neuronal damage, reduced opening of the BBB, and accelerated weight regain. CCR2 antagonists are efficacious after traumatic brain injury (45) and have entered clinical trials for neuropathic pain treatment (66). We propose that selective targeting of myeloid cell subsets via chemokine receptors will allow manipulation of specific immune cell types in the brain after injury or during disease.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Morganti and colleagues recently evaluated a CCR2 antagonist (CCX872) in CX3CR1GFP/+CCR2RFP/+ reporter mice using the 34 CCR2 antagonism also improved cognitive function recovery after TBI, as demonstrated by increased performance of CCX872-treated mice in a radial arm water maze test at 28 days post-injury. 34 They also showed that CCR2-positive infiltrating macrophages in the brain expressed both M1-and M2-like markers acutely after TBI, with sequential activation of M1-, followed by M2a-, and finally M2c-marker expression. 34 However, the accumulation of CCR2-positive macrophages into the TBI brain ultimately resulted in up-regulation of pro-inflammatory M1-like cells with neurotoxic potential, and CCR2 antagonism robustly reduced this pro-inflammatory profile and ameliorated the long-term cognitive dysfunction induced by TBI.…”
Section: Fig 7 (Continued)mentioning
confidence: 94%
“…34 However, the accumulation of CCR2-positive macrophages into the TBI brain ultimately resulted in up-regulation of pro-inflammatory M1-like cells with neurotoxic potential, and CCR2 antagonism robustly reduced this pro-inflammatory profile and ameliorated the long-term cognitive dysfunction induced by TBI. 34 These studies highlight a significant contribution of infiltrating macrophage to polarization after TBI, and further research is needed to understand mechanisms driving the trafficking of macrophages subsets to the TBI brain, how they interact with and modulate resident glial cells (microglia and astrocytes), and their role in chronic neurodegeneration following TBI.…”
Section: Fig 7 (Continued)mentioning
confidence: 99%
“…We hypothesized that TBI-induced sustained eIF2α phosphorylation in the hippocampus, a brain region crucially involved in memory formation, could be a major contributor to the permanent cognitive dysfunction observed after TBI (34). To test this notion, we investigated whether treatment with ISRIB, several weeks postinjury, could remedy TBI-induced impairments in cognitive function and associated changes in synaptic function.…”
mentioning
confidence: 99%